Digital Marketing Strategy Model in Integration of the Industrial Revolution 4.0 - Febrianto, Dany; Handoko, Fourry; Vitasari, Prima (Journal of Management, 2025)
In the era of Industrial Revolution 4.0, alternative marketing technologies play a crucial role in determining effective strategies for product marketing. These innovations help business actors better understand, monitor, and respond to consumer needs and preferences. From the consumer perspective, digital platforms provide easier access to product information. However, Radio City Guide FM still faces challenges in developing strategic approaches that align with its performance goals, particularly amid financial constraints. This study aims to examine the implementation of Radio City Guide’s management strategies in the context of Industry 4.0. The research employs a purposive sampling method targeting active listeners, with variables measured using a Likert scale. Factors considered include job characteristics, frequency of listening, domicile, and age. A total of 161 respondents were included in the sample. Five key variables were identified as determinants of digital marketing success: knowledge, innovation skills, digital utility, frequency, and demographic factors. The results indicate that knowledge is a particularly influential factor in determining digital marketing effectiveness. Additionally, the study finds that City Guide FM’s audience is largely composed of individuals in their productive years who are technologically literate. These insights are expected to support the development of innovative and adaptive marketing strategies for radio broadcasting in the digital era.